The European Model of Organizational Excellence as a Tool for Retaining Talent An exploratory study of sample views of the administrative leaders at Erbil Polytechnic University - Al-Margahi, James Y. O.; Al-Mahmood, Saad F. A. (Humanities Journal of University of Zakho, 2018)
The current research seeks to define the European model of organizational excellence role in the retaining Talent through the field testing of sample data from the administrative leaders at Erbil Polytechnic University. The researchers built a default model benefiting from the theoretical literature of the subject, which deals with the nature of the correlation and influence between the research variables represented by the European model of organizational excellence and retaining Talent. On the basis of this, two main hypotheses and sub-hypotheses were formulated. The data collected through questionnaire, which was distributed to the administrative leaders at Erbil Polytechnic University, and it was analyzed by using a set of statistical methods. The research found a number of conclusions, the most important of which was the possibility of using Erbil Polytechnic University the European model of organizational excellence as a tool for retaining Talent due to the existence of a positive correlation and impact between them, and operations are one of the most criterion of the models has correlation and influential in retaining Talent. While the most important suggestions indicate that the survival of Erbil Polytechnic University and success to get good reputation is linked to the ownership of Talent, which is a competitive advantage of sustainable because it can achieve creativity and innovation in the performance of its functions, so the University must increase its interest in the retaining Talent.